KOMPYUTER GRAFIKASINI O’RGATISHDA AMALIY DASTUR ISHLAB CHIQISH - O‘razboyev, N.U.; Madaminov, U.A.; Avezov, M.A. (SCIENCE and SOCIETY, 2020)
This article presents the benefits of computer graphics, including two-dimensional and three-dimensional programming. Today there are many 2D and 3D computer programs. One of them is a JavaFX program. This program allows you to create object models and two-dimensional, three-dimensional graphics using a programming language.